THE EFFECTIVENESS OF VIDEO-MAKING TASK IN INCREASING STUDENTS’ SPEAKING SKILL - Dewi khawa (Graduate Program, University of Islam Malang, 2020)
This study used quasi-experimental research design to investigate the effectiveness of video-making task in students speaking skill. The study conducted in UPT Bahasa IAIDA Blokagung Banyuwangi during corona virus pandemic on April 2020. The sample was second semester students of Arabic department. There were 45 students involved the study; 22 students of experiment class and 23 students of control class. In pre-test, students’ speaking skill in experiment and control class was revealed on the same level. The treatment was held online in four meetings. Experiment class was given video-making task and control group was drilled by using audio-lingual method. In experimental class, tutor gave the theme and asked students to make video about the theme and upload it on social media. In post-test, students were called via WhatsApp video and asked to explain about themselves in 5 minutes. The data of pre-test and post-test was analyzed by using independent sample t-testSPSS2.0. The result showed that video-making task significantly effective in increasing students’ speaking score.